The versatility of Penicillium species to degrade organic pollutants and its use for wastewater treatment - Wolski, Erika Alejandra (2023)
The removal of xenobiotics from industrial wastewater is of great interest to avoid environmental contamination. Penicillium species have been shown to be able to adapt its metabolism to many different circumstances and these fungi can use different xenobiotics as a carbon source. In this review, the ability of Penicillium to degrade different xenobiotic compounds is discussed. This review describes not only the biodegradation processes but also addresses the toxicity of the degradation products as well as the potential application of these processes in wastewater treatment. Penicillium strains have proven to be versatile and capable of being used for the biodegradation of different organic pollutants (phenols, azo dyes, hydrocarbons, pharmaceutical compounds, etc.) and show high potential to be used for wastewater treatment. From this review, it is concluded that beyond the degradation and optimization processes; pilot scale studies and toxicity must be carried out.